Perlindungan Hukum Terhadap Pekerja Harian Lepas Pada Perusahaan Yang Bergerak Dalam Bidang Logistik - Aura Syahranni; Dita Cahyani Sudirman; Halimah Citra Negoro; Nabila Alya Husna; Nadila Khairunnisa; Qristiana Qristiana; Salsabilla Putri Alaika; Sri Juwita Putri; Mustika Mega Wijaya (Jurnal Relasi Publik, 2023)
This increase is very important for a country, especially for a developing country like Indonesia. Along with continuous improvement, progress is characterized as a conscious effort by the state. One of the things that is very important in the progress of a nation is its workers, that in the rapid progress of a country, it is the workers who start. That departing from this, the government is an important part in winning progress in the business sector as well as for the national development program which must be endeavored to open up as many jobs as possible from various layers of trade that are able to balance the increase in quality and increase in security for the workforce which can become a must. Whereas Article 27 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that "Every citizen has the right to work and a life worthy of humanity". This research is descriptive in nature which aims to collect data as thoroughly as possible that can accurately describe the legal protection of casual daily workers. The type of research used by the authors uses the type of empirical normative legal research. With library and field research data collection techniques. Problems that arise in the use of legal guarantees for precarious workers/laborers are the factors contained in the components of labor instructions, the labor economy as a result of not partnering with trade unions, and based on variables from employers/companies that have not been maximized in implementing legal security in understanding of the labor inspection in force in Indonesia and elements from the government's point of view that are lacking in providing outreach, supervision and firm action against companies that are naughty in running their business which can harm casual daily workers.